CD34+DNAM-1brightCXCR4+ haemopoietic precursors circulate after chemotherapy, seed lung tissue and generate functional innate-like T cells and NK cells - Perrone, Carola; Bozzano, Federica; Dal Bello, Maria Giovanna; Del Zotto, Genny; Antonini, Francesca; Munari, Enrico; Maggi, Enrico; Moretta, Francesca; Farshchi, Alireza Hajabbas; Pariscenti, Gianluca; Tagliamento, Marco; Genova, Carlo; et al. (Frontiers in Immunology, 2024)
Background: There is little information on the trajectory and developmental fate of Lin - CD34 + DNAM-1 bright CXCR4 + progenitors exiting bone marrow during systemic inflammation.Objective: To study Lin -CD34 + DNAM-1 bright CXCR4 + cell circulation in cancer patients, to characterize their entry into involved lung tissue and to characterize their progenies.Methods: Flow cytometric analysis of PBMC from 18 patients with lung cancer on samples collected immediately before the first and the second treatment was performed to study Lin -CD34 + DNAM-1 bright CXCR4 + precursors. Precursors were purified (>99%) and cultured in vitro from all patients.Paired PBMC and tissue samples from patients undergoing tumor resection were analyzed by flow cytometry to assess tissue entry and compare phenotype and developmental potential of Lin - CD34 + DNAM-1 bright CXCR4 + cells in both compartments.Results: significant circulation of Lin -CD34 + DNAM-1 bright CXCR4 + precursors was observed 20d after the first treatment. Precursors express CXC3CR1, CXCR3, CXCR1 consistent with travel towards inflamed tissues. Flowcytometric analysis of lung tissue samples showed precursor presence in all patients in tumor and neighboring uninvolved areas. Successful purification and in vitro culture from both blood and lung tissue generates a minor proportion of maturing NK cells (<10%) and a predominant proportion (>85%) of α/β T-progenies with innate-like phenotype expressing NKG2D,NKp30,DNAM-1. Innate-like maturing T-cells in vitro are cytotoxic, can be triggered via NKR/TCR co-stimulation and display broad spectrum Th1,Th2 and Th1/Th17 cytokine production Conclusion: in advanced stage lung cancer CD34 + DNAM-1 bright CXCR4 + inflammatory precursors increase upon treatment, enter involved tissues, generate functional progenies and may tus represent an additional player contributing to immune balance in the highly SDF-1/CXCR4-biased pro-metatsatic tumor microenvironment